Corporate finance : theory and practice in emerging economies - Mahajan, Sunil, 1961- (Cambridge : Cambridge University Press, 2020)
The book introduces corporate finance to first year students in business schools. Basic subjects such as marketing, human resources and finance are all fundamental to the learning of a business manager. A book on these subjects must emphasise learning that is conceptual in nature and at the same time, application oriented. This book attempts to achieve this in a manner that is comprehensive and shorn of complexity. It examines the practice of finance without diluting theory and conceptual knowledge. Corporate finance is necessarily quantitative in nature and the book duly places emphasis on that aspect. It ensures the primacy of ideas and concepts utilising numbers as supportive elements.
Title from publisher's bibliographic system (viewed on 04 May 2020).
Keywords: Corporations -- Developing countries -- Finance; Business enterprises -- Developing countries -- Finance